2003
DOI: 10.1002/fam.819
|View full text |Cite
|
Sign up to set email alerts
|

Charring rates and temperature profiles of wood sections

Abstract: SUMMARYA research project was carried out at the Swiss Federal Institute of Technology (ETH) to study the fire behaviour of hollow core timber slabs and timber-concrete composite slabs. This paper describes the main results of the basic fire behaviour of timber measured in the study. The first part of the analysis looks at the charring rate of timber. In the second part a new calculation model for the temperature development in wood members exposed to the standard ISO-fire is presented and compared with the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
112
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 114 publications
(122 citation statements)
references
References 1 publication
7
112
0
3
Order By: Relevance
“…8, significantly affects both the out-of-plane deflections and time-to-failure predictions. The sensitivity of the time-to-failure predictions to the residual elastic modulus was determined by comparing the predicted and observed times-to-failure for all intermediate-scale tests performed by Summers [21]. The results are similar to that shown in Fig.…”
Section: Sensitivity Of Model Predictionssupporting
confidence: 72%
See 1 more Smart Citation
“…8, significantly affects both the out-of-plane deflections and time-to-failure predictions. The sensitivity of the time-to-failure predictions to the residual elastic modulus was determined by comparing the predicted and observed times-to-failure for all intermediate-scale tests performed by Summers [21]. The results are similar to that shown in Fig.…”
Section: Sensitivity Of Model Predictionssupporting
confidence: 72%
“…This concept may be applied to FRP laminates, though, as for timber, the heat flux and convective conditions will affect the charring rate [21]. Mouritz and Mathys [22] determined that the rate of growth of the char layer thickness is non-constant over time and is dependent on both the exposure time and applied heat flux for FRP laminates.…”
Section: Thermal Model Developmentmentioning
confidence: 99%
“…The char layer is a good insulator and protects the remaining uncharred residual cross-section against heat. For timber surfaces unprotected throughout the time of fire exposure, the charring rate can be assumed constant with time [4]. As a basic value, the one-dimensional charring rate β 0 is usually taken as the value observed for one-dimensional heat transfer under ISO-fire exposure in a semi-infinite timber slab.…”
Section: Charring Of Timbermentioning
confidence: 99%
“…The same effects were observed for connections D1.3 and D1.4 protected by timber boards and gypsum plasterboards, respectively. The analysis of the residual cross-sections of all test specimens showed that the charring depth measured in section A-A (located close to the connection) corresponded to a charring rate of about 0.7 mm/min on all four sides and agrees well with values measured in several experimental studies [18][19][20]. The charring depth measured in section B-B (located in the connection) corresponded to a charring rate varying between 0.8 and 0.9 mm/min on the top and bottom and between 1.0 and 1.2 mm/ min on the sides.…”
Section: Residual Cross-sectionmentioning
confidence: 67%